Modern possibilities of ovarian endometrioid cyst treatment - I A Lapina; Yu E Dobrokhotova; M V Gavrilov; A S Sdvigov; N S Ermolenko (IP Berlin A.V., 2017)
The aim of the study was to evaluate the effectiveness of the procedure of removing endometrioid cysts using the PerClot local haemostatic system for the maintenance of healthy ovarian tissue, as well as revealing the possible systemic effect of this drug on hemostasis. Materials and methods. A controlled clinical randomized prospective study was conducted, targeting 82 women of reproductive age with endometrioid ovarian cysts. All patients underwent surgical treatment. The method of simple randomization of women was divided into two groups: 1 group (main) consisted of 32 women who were removed the capsule of the cyst, followed by treatment of the bed with the haemostatic system Perclot. The second group consisted of 50 patients who had been removed from the endometrioid cyst according to the traditional method, including a complete excision of the capsule, and as a hemostasis bipolar electrosurgery was used. The control group consisted of 40 healthy women of reproductive age. All participants in the study conducted a comprehensive clinical laboratory and instrumental examination. Results and conclusions. The data obtained suggest that the local method of using the new generation of hemostatic, PerClot, allows quickly and effectively to stop bleeding in combination with a low traumatic effect on healthy ovarian tissue, thereby allowing the preservation of its follicular reserve, which is especially effective in patients with endometriomas 5 cm.